On the Sputtering of Titanium and Silver onto Liquids, Discussing the Formation of Nanoparticles - Carette, Xavier; Debièvre, Benoît; Cornil, David; Cornil, Jérôme; Leclère, Philippe; Maes, Bjorn; Gautier, Nicolas; Gautron, Eric; El Mel, Abdel-Aziz; Raquez, Jean-Marie; Konstantinidis, Stephanos (Journal of physical chemistry. C, 2018)
Titanium and silver atoms were magnetron-sputtered either onto pentaerythritol ethoxylate (PEEL) or 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIMTFSI) ionic liquid (IL), and the formation of nanoparticles (NPs) is discussed based on the chemical interaction between the metal atoms and the host liquid. In the case of PEEL, our data reveal that titanium atoms sputtered in low-pressure argon plasma first form a film over the liquid surface. However, the latter dissolves as the film gets oxidized when vented to the air; asymmetric and faceted titanium dioxide NPs are finally obtained as if they were originating from a dismantled polycrystalline thin film. In the case of silver sputtered on PEEL, a film forms and solvation never occurs even after exposing the sample to air because the oxidation of silver is thermodynamically much less favorable than titanium. Quantum-chemical calculations confirm that the chemical interaction of TiO2 with PEEL molecules is favored as compared to metallic Ag or Ti. In contrast to what is observed with PEEL, when silver is sputtered onto the BMIMTFSI IL, no film is observed and spherical and crystallized silver NPs are found. These results suggest that the Ag-NP grows inside the IL because the chemical interaction of the Ag atoms with the BMIMTFSI molecules is highly favorable.